Investigation of Mechanical Properties of Basalt Particle-Filled SMC Composites - Kadir Cavdar; Mahmut Bingol (International Journal of Polymer Science)
Basalt particles have been investigated as a novel additive for the production of glass fibre reinforced composite using sheet moulding compound (SMC) method. Compared to the CaCO3 that are widely used as filler in the SMC composite, the resulting composites exhibit improved mechanical properties. The tensile strength increased by approximately 15%, whereas the flexural strength was enhanced by 8% in SMC composites prepared by basalt particles. Examination of the surface morphology and interfacial debonding of the specimens is also performed via scanning electron microscopy. Superior strength properties are observed in the basalt particle-reinforced composites compared to those with the CaCO3 fillers.